Tuan
Giới thiệu về bản thân
-14 - x + (-15) = -10
-29 - x = -10
x = (-29) - (-10)
x = -19
8x3 - 36x2 + 54x - 26 = 0
8x3 - 8x2 - 28x2 + 28x + 26x - 26 = 0
8x2(x - 1) - 28x(x - 1) + 26(x - 1) = 0
(x - 1)(8x2 - 28x + 26) = 0
x - 1 = 0 hoặc 8x2 - 28x + 26 = 0
TH1: x - 1 = 0
x = 1
TH2: 8x2 - 28x + 26 = 0 (vô nghiệm)
Vậy x = 1
2x(2-y) - 10 + 5y
= 4x - 2xy - 10 + 5y
= (4x - 10) - (2xy - 5y)
= 2(2x - 5) - y(2x - 5)
= (2 - y)(2x - 5)
Dấu hiệu chia hết cho 3: Tổng các chữ số chia hết cho 3 thì số đó chia hết cho 3
nên x+5+6+7 ⋮ 3
x+18 ⋮ 3
suy ra x ⋮ 3
vậy x = 3, x= 6 hoặc x= 9
CH2=AC2-AH2 (PTG)
(AH2=AB2-HB2)
CH2=AC2-(AB2-HB2)
CH2-HB2=AC2-AB2
(CH+HB)(CH-HB)=AC2-AB2
BC.[CH-(BC-CH)]=AC2-AB2
BC.(2CH-BC)=AC2-AB2
2CH.BC=BC2+AC2-AB2
CH=(BC2+AC2-AB2):2BC